Management of pre‐, peri‐, and post‐menopausal abnormal uterine bleeding: When to perform endometrial sampling? - Papakonstantinou, Efthymia; Adonakis, Georgios (International journal of gynecology and obstetrics, 2022)
Abnormal uterine bleeding (AUB) is defined as abnormal volume, duration, or frequency of menstrual period and is a common symptom in women of all ages (premenopausal, perimenopausal, and postmenopausal). The acronym PALM‐COEIN, introduced by the International Federation of Gynecology and Obstetrics (FIGO), facilitates the evaluation and differential diagnosis of AUB, mostly in premenopausal women with AUB. Endometrial evaluation (including ultrasound or hysteroscopic imaging and tissue sampling) for subtle pathology is proposed in patients who are at high risk for endometrial cancer and in patients at low risk who present with AUB and who present poor correspondence in medical treatment. Many new diagnostic modalities are available in clinicians in order to help the assessment of women presenting with abnormalities in their menstrual pattern. The present study reviews the optimal management of women presenting with AUB, taking into consideration the actual need for invasive management in these women, who of them require it, and who can be diagnosed without histological verification. The importance of endometrial tissue sampling in women who present with AUB as well as the best timing for a clinician to conduct a biopsy are two axons analyzed below, according to the latest worldwide guidelines and major publications about this subject. A brief mention, addressing clinicians, of the latest guidelines and data concerning the significance of endometrial sampling (biopsy) in women with abnormal uterine bleeding.